2020
DOI: 10.1123/ijspp.2019-0433
|View full text |Cite
|
Sign up to set email alerts
|

What Dose of Caffeine to Use: Acute Effects of 3 Doses of Caffeine on Muscle Endurance and Strength

Abstract: Purpose: To explore the effects of 3 doses of caffeine on muscle strength and muscle endurance. Methods: Twenty-eight resistance-trained men completed the testing sessions under 5 conditions: no-placebo control, placebo control, and with caffeine doses of 2, 4, and 6 mg·kg−1. Muscle strength was assessed using the 1-repetition-maximum test; muscle endurance was assessed by having the participants perform a maximal number of repetitions with 60% 1-repetition maximum. Results: In comparison with both control con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 31 publications
5
42
0
2
Order By: Relevance
“…The muscle endurance test used in this study further confirmed that caffeine ingestion is ergogenic for this fitness component in resistance-trained men. This study adds to the body of evidence showing improvements in muscle endurance following caffeine ingestion [28][29][30][31][32]. However, a more novel finding is that caffeine is ergogenic for power and velocity outputs when the number of repetitions between the caffeine and placebo conditions is matched.…”
Section: Effects Of Caffeine On Exercise Performancementioning
confidence: 75%
See 2 more Smart Citations
“…The muscle endurance test used in this study further confirmed that caffeine ingestion is ergogenic for this fitness component in resistance-trained men. This study adds to the body of evidence showing improvements in muscle endurance following caffeine ingestion [28][29][30][31][32]. However, a more novel finding is that caffeine is ergogenic for power and velocity outputs when the number of repetitions between the caffeine and placebo conditions is matched.…”
Section: Effects Of Caffeine On Exercise Performancementioning
confidence: 75%
“…However, as we demonstrated in the present study, even with an equal number of repetitions between conditions, caffeine might have still produced considerable improvements in the quality of the performed repetitions, that is, greater movement velocity and consequently, greater power output (which was not tested in the aforementioned studies). As compared to placebo, caffeine ingestion most commonly produced moderate improvements in the number of performed repetitions (generally one to three additional repetitions) [28,31]. We propose that in some contexts, improvements in the overall quality of the performed repetitions may be more important for training adaptations than simply performing a greater number of repetitions.…”
Section: Effects Of Caffeine On Exercise Performancementioning
confidence: 87%
See 1 more Smart Citation
“…Capsules were prepared in the laboratory by an experienced researcher while other researchers performed the blinding. Capsules were ingested 60 min before the start of the exercise session under the supervision of the research staff, as in previous research [1,26,27]. The participants' genotype was determined using a buccal swab.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although habitual coffee drinking can enhance performance, the daily amount of coffee consumption in our older participants was relatively low [median] about two small cups or 220 g/day. As some studies have reported that athletes did not get extra benefit for their performance by consuming much higher amounts of coffee per day [19], a recent study showed that even low acute dose of caffeine (2 mg/ kg for 80 kg individual) that equal to approximately 200 g of coffee a day may produce substantial improvements in lower body muscle endurance [20]. Coffee also contains several bioactive compounds such as polyphenols and minerals and up to 1000 other bioactive components that could potentially affect performance and prevent chronic diseases.…”
Section: Discussionmentioning
confidence: 99%